Phylogeny of the genera Euclidiodes and Hasodima (Lepidoptera: Geometridae) and description of two new species from the Fray Jorge relict forest in northern Chile - Parra, Luis E.; Villagrán-Mella, Romina; Marquet, Pablo A. (Zootaxa, 2009)
The Fray Jorge National park contains the northernmost temperate relict forest of Chile (30º40’S), located over 1000 kilometers north of the rest of the coastal Aextoxicon punctatum (olivillo) communities of southern Chile. In this work we describe two new species of moths in the Fray Jorge relict forest belonging to the genera Hasodima Butler 1882 and Euclidiodes Warren 1895: H. ediliacarmenae Parra sp. nov. and E. frayjorgeana Parra sp. nov. The sister species of these new taxa are distributed in the central-southern zone of Chile, in plant associations where the olivillo is present. We hypothesize that the ancestor from which these species derived was widely distributed in association with coastal “olivillo” forests, which became restricted in distribution during interglacial periods, resulting in the isolation of these insects’ populations, and their subsequent speciation.